A history of the Andrews railroad raid into Georgia in 1862 : embracing a full and accurate account of the secret journey to the heart of the confederacy, the capture of a railway train in a Confederate camp, the terrible chase that followed, and the subsequent fortunes of the leader and his party - Pittenger, William, 1840-1904 (Digital Scanning, 2000)
Based on the original 1863 true story, Daring and Suffering, this 1887 version of the Andrews Railroad raid by Union soldiers embraces a full and accurate account of this secret journey to the heart of the confederacy. Pittenger, the author, recalls his story of the secret raid to cut the rail link between Marietta and Chattanooga, his capture and the subsequent prisoner exchange program that set him free. He and the other survivors were the first soldiers with the rank of Private to be awarded the Congressional Medal of Honor.